1986
DOI: 10.1542/peds.78.3.423
|View full text |Cite
|
Sign up to set email alerts
|

Otitis Media in Early Childhood and Its Relationship to Later Verbal and Academic Performance

Abstract: The relationship between the occurrence of otitis media with effusion during the first 3 years of life and subsequent verbal and academic performance was examined in 61 socioeconomically disadvantaged children who attended a research day-care program. Study children were participants in a longitudinal study of child development in which the number of episodes of otitis media and duration of each otitis episode were reported prospectively from infancy. The incidence of otitis media was highest during the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…OM has also been associated with later academic difficulties (Brandes & Ehinger, 1981;Silva et al, 1986;Zinkus & Gottlieb, 1980). In contrast with such findings, other studies have failed to document this relation (e.g., Hubbard, Paradise, McWilliams, Elster, & Taylor, 1985;Roberts et al, 1986;Wright et al, 1988).…”
mentioning
confidence: 89%
“…OM has also been associated with later academic difficulties (Brandes & Ehinger, 1981;Silva et al, 1986;Zinkus & Gottlieb, 1980). In contrast with such findings, other studies have failed to document this relation (e.g., Hubbard, Paradise, McWilliams, Elster, & Taylor, 1985;Roberts et al, 1986;Wright et al, 1988).…”
mentioning
confidence: 89%
“…They also found that children with a hearing loss of 20 dB or greater during episodes of otitis media had poorer scores on the SICD when they were well. A few other studies have also found some effect on early language development (Teele et al, 1984; Wallace, Gravel, McCarton, & Ruben, 1988), but there is much less support for long-term effects on basic language skills (Fischler, Todd, & Feldman, 1985; Roberts et al, 1986).…”
mentioning
confidence: 96%